Total Site Hydrogen Integration with fresh hydrogen of multiple quality and waste hydrogen recovery in refineries. (19th March 2022) - Gai, Limei; Varbanov, Petar Sabev; Fan, Yee Van; Klemeš, Jiří Jaromír; Nižetić, Sandro
Abstract: This paper proposes a novel method combining Pinch Methodology and waste hydrogen recovery, aiming to minimise fresh hydrogen consumption and waste hydrogen discharge. The method of multiple-level resource Pinch Analysis is extended to the level of Total Site Hydrogen Integration by considering fresh hydrogen sources with various quality. Waste hydrogen after Total Site Integration is further regenerated. The technical feasibility and economy of the various purification approaches are considered, demonstrated with a case study of a refinery hydrogen network in a petrochemical industrial park. The results showed that fresh hydrogen usage and waste hydrogen discharge could be reduced by 21.3% and 67.6%. The hydrogen recovery ratio is 95.2%. It has significant economic benefits and a short payback period for Total Site Hydrogen Integration with waste hydrogen purification. The proposed method facilitates the reuse of waste hydrogen before the purification process that incurs an additional environmental footprint. In line with the Circular Economy principles, hydrogen resource is retained in the system as long as possible before discharge. Graphical abstract: Image 1 Highlights: Integration and recovery of hydrogen in networks at Process and Total Site context. Consideration of fresh hydrogen sources at different quality levels. Hydrogen Pinch Analysis is extended to Total Site scope and multiple-level fresh sources. Sustainable waste hydrogen recovery design by techno-economic performance. The case study reduced fresh hydrogen and waste hydrogen by 21.3% and 67.6%.